The Edinburgh companion to the Bible and the arts - Prickett, Stephen (Edinburgh University Press, 2014)
Examines the changing relationship between the Bible and the arts, showing how the arts portray biblical stories in various ways and through various media, and how 'the' Bible is actually multiple entities: fiercely contested translations in many languages. Generously illustrated with examples including painting, architecture and stained glass.